Joint consultative committee practice and organisational culture at three public universities in Malaysia - Badariah Ab Rahman (2019)
This thesis discusses on the JCC practice in public universities in Malaysia through the Academic Staff Associations (Academic JCC) in three public universities in Malaysia. The research has four objectives. Firstly, to explore the establishment of the Academic JCCs practices that had influence the organisational culture of public universities in Malaysia. Secondly, to investigate the contending factors faced by the Academic JCCs in public universities in Malaysia. Thirdly, to examine the role of organisational culture in influencing the effectiveness of the Academic JCC in public universities in Malaysia. Fourthly, to analyse the importance of the Academic JCC practices in influencing the decision making process in public universities in Malaysia. The methodology applied was qualitative case study design primarily using in-depth interview techniques and secondary data obtained from various method. The major findings were divided into few sections. First, the AUKU, 1971 and Service Circular No. 2 Year 1992 are the fundamental document for the relationship between the Academic JCC and management that shaped the organisational culture. Second, women participation was lacking in UPP, UPK, and UBS. Third, the influence of the Academic JCC to the organisational culture differs in UPP, UPK, and UBS. Fourth, the Academic JCCs can exert some influence to the organisational culture decision making process. A new finding emancipated through this was the participation of women in the Academic JCCs was not relevant to the present organisational culture of the public universities. The findings leads to the loose partnership arrangement made between the Academic JCCs-management and vice versa. This result warrants to some amendments toward the current policy with regards to the role and function of the Academic JCCs because it is important for the two parties to work in partnership instead of being treated as separate entities in organisations with conflicting objectives. This research has established that the desire to move forward is being felt but still concerned with who is the authority (power). As long as this power game is the case, this research argues that the management will continue to make final decisions; thus will preserve its supremacy as the single authority in public universities in Malaysia.